Anti–Interleukin-6 and Janus Kinase Inhibitors for Severe Neurologic Toxicity of Checkpoint Inhibitors. Issue 6 (November 2021) - Picca, Alberto; Valyraki, Nefeli; Birzu, Cristina; Kramkimel, Nora; Hermine, Olivier; Zahr, Noel; Berzero, Giulia; Psimaras, Dimitri
Abstract : Background and Objectives: To describe the marked clinical and biological responses of a targeted treatment with anti–interleukin-6 (IL-6)–receptor antibody and Janus kinase (JAK) inhibitors in a patient with a severe, corticoresistant CNS toxicity of immune-checkpoint inhibitor (ICI) therapy. Methods: A 58-year-old man was admitted for subacute paraparesis, urinary retention, and ascending paresthesia. He was under treatment with ipilimumab and nivolumab for metastatic melanoma. Spine MRI disclosed multiple T2-hyperintense, contrast-enhancing longitudinally extensive lesions. A diagnosis of ICI-related acute transverse myelitis was made. Results: ICIs were immediately discontinued, and the patient received high-dose glucocorticoids plus 1 session of plasma exchange, but he did not improve. Based on the marked elevation of CSF IL-6 (505 pg/mL), a second-line targeted therapy with anti-IL-6-receptor tocilizumab (8 mg/kg/mo for 3 infusions) plus JAK inhibitor ruxolitinib (50 mg/d) was administered. Patient neurologic status started to improve shortly after, with corresponding radiologic resolution. At 9 months, the patient was able to walk independently, presenting only slight residual disability while remaining in oncologic partial response. Discussion: Our case suggests that some patients with severe, corticoresistant CNS immune-related toxicities of ICIs may benefit from cytokine blockade. Cytokine measurement in serum and CSF might help in selecting patients for personalized treatment strategies.